ANALISIS PENGARUH STOCK SPLIT TERHADAP HARGA SAHAM, VOLUME PERDAGANGAN DAN ABNORMAL RETURN PADA PERUSAHAAN BERTUMBUH DAN TIDAK BERTUMBUH - Tiya Mardiyati Dalimunthe; Zulbahridar -; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to obtain empirical evidence and to analyze the differences in stock price, trading volume, and the abnormal return on the growth company and ungrowth company before and after the stock split announcement. This study uses 64 companies listed on the Indonesian Stock Exchange (BEI) that the stock-split in the range of 2007-2014. Sum of 53 companies for growth sample’s companies, and 11 sample firms for ungrowth companies. Categorizing the growth and ungrowth companies using IOS (Investment Opportunity Set) proxy MVEBVE (Market to Book Value of Equity). Data collection techniques in this study is done by using purposive sampling method based on secondary data that are available in the Indonesia Stock Exchange website. The method of analysis used Wilcoxon signed rank test and Mann-Whitney test with IBM SPSS version 20 for Windows. Research shows that there are significant differences in the average stock price of ungrowth company, the average TVA on growth company, AAR on growth company and ungrowth companies before and after the stock split and the average stock price and the average TVA between the growth company and ungrowth company after the stock split. Where significant difference were not found in the average stock price of growth company, the average TVA of ungrowth companies before and after the stock split and the AAR between the growth companies and the ungrowth companies after stock split.Keywords: stock split, stock price, TVA, AAR, growth, and ungrowth company